Recent Developments and Applications of Hemicellulose From Wheat Straw: A Review - Huang, Ling-Zhi; Ma, Ming-Guo; Ji, Xing-Xiang; Choi, Sun-Eun; Si, Chuanling (Frontiers in Bioengineering and Biotechnology, 2021)
Hemicellulose is an important component of plant cell walls, which consisted of a heterogeneous group of plant-derived polysaccharides including D-xylose, D-mannose, D-galactose, and L-arabinose, D-galactose, and 4-O-methyl-D-glucuronic acid. The hemicellulose extracted from different plant sources and plant locations has different microstructure and molecule. Wheat straw is an important biomass raw material for the extraction of hemicellulose. This review paper aims to summary the recent developments and various applications of hemicellulose from wheat straw. The microstructure and molecule of hemicellulose extracted by different methods are comparably discussed. The hemicellulose-based derivatives and composites are also reviewed. Special attention was paid to the applications of hemicellulose such as biofuel production, packaging field, and adsorbent. The problem and develop direction are given based on our knowledges. We expect that this review will put forward to the development and high-value applications of hemicellulose from wheat straw.